2020
DOI: 10.3389/fnhum.2020.00163
|View full text |Cite
|
Sign up to set email alerts
|

Early Engagement of Parietal Cortex for Subtraction Solving Predicts Longitudinal Gains in Behavioral Fluency in Children

Abstract: There is debate in the literature regarding how single-digit arithmetic fluency is achieved over development. While the Fact-retrieval hypothesis suggests that with practice, children shift from quantity-based procedures to verbally retrieving arithmetic problems from long-term memory, the Schema-based hypothesis claims that problems are solved through quantity-based procedures and that practice leads to these procedures becoming more automatic. To test these hypotheses, a sample of 46 typically developing chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 111 publications
(176 reference statements)
1
8
0
Order By: Relevance
“…The finding of this association only for younger children may suggest that brain structure of the left IPS is important early on because children rely more on quantity-based calculation strategies, whereas older children tend to retrieve the solution from long-term memory. Using fMRI, a previous study showed no evidence for such a shift, with no involvement of retrieval-related brain regions predicting subtraction gains ( Suárez-Pellicioni et al, 2020 ). Our results are more likely due to the younger group relying on quantity mechanisms to compute the calculations required to solve the subtraction test, while older children may have automatized these procedures ( Fayol and Thevenot, 2012 ; LeFevre et al, 2006 ).…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…The finding of this association only for younger children may suggest that brain structure of the left IPS is important early on because children rely more on quantity-based calculation strategies, whereas older children tend to retrieve the solution from long-term memory. Using fMRI, a previous study showed no evidence for such a shift, with no involvement of retrieval-related brain regions predicting subtraction gains ( Suárez-Pellicioni et al, 2020 ). Our results are more likely due to the younger group relying on quantity mechanisms to compute the calculations required to solve the subtraction test, while older children may have automatized these procedures ( Fayol and Thevenot, 2012 ; LeFevre et al, 2006 ).…”
Section: Discussionmentioning
confidence: 86%
“…Whereas the higher the GMV in left IPS at T1 the more they gained in subtraction skill, the higher the GMV in the left MTG/STG at T1 the less they gained in this operation. This finding suggests that structural integrity of quantity representation regions in the brain is what explains improvement in this operation, whereas the structural integrity of verbal representation regions, which potentially could have facilitated the use of the retrieval strategy, seems to be detrimental to improvement in this operation ( Suárez-Pellicioni et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations